The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/jdd.12943
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the experience of dental students with an asynchronous online course about racism, cultural competence

Abstract: SP2) designed an asynchronous online course about racism and cultural competence to address student concerns about harmful interactions with peers across race/ethnicity. The Penn Experience Course establishes common language and concepts to facilitate difficult conversations about racism in the classroom and clinical spaces. Methods: The course included six modules addressing the history of racism in the Philadelphia area and at the University of Pennsylvania: implicit bias and microaggressions; racism and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…In the fall of 2019, two faculty members from Penn's School of Social Policy and Practice (SP2) and Penn School of Dental Medicine (PDM) began collaborating on the development of an online, asynchronous course for incoming students about racism (Crawford & Hillier, 2022). SP2 has required graduate social work students to complete a two-course sequence in American racism for 50 years (Arnold, 1970), but faculty and staff still struggled to address concerns from students of color about the emotional burden of discussing racism in predominantly White classrooms.…”
Section: Development Of the Penn Experience Coursementioning
confidence: 99%
See 1 more Smart Citation
“…In the fall of 2019, two faculty members from Penn's School of Social Policy and Practice (SP2) and Penn School of Dental Medicine (PDM) began collaborating on the development of an online, asynchronous course for incoming students about racism (Crawford & Hillier, 2022). SP2 has required graduate social work students to complete a two-course sequence in American racism for 50 years (Arnold, 1970), but faculty and staff still struggled to address concerns from students of color about the emotional burden of discussing racism in predominantly White classrooms.…”
Section: Development Of the Penn Experience Coursementioning
confidence: 99%
“…A total of 427 students completed the course evaluation between July and December 2020. Matched pre–post results showed that students were more likely to engage with the neighborhoods near campus and more confident about talking with peers in class about topics such as White supremacy, gentrification, microaggressions, and restorative justice after completing the course (Crawford & Hillier, 2022). Open-ended survey responses reflected a generally positive experience for most students, including appreciation for the convenient format, professional relevance, and opportunity to increase their knowledge about Philadelphia and at Penn.…”
Section: Student Learning and Feedbackmentioning
confidence: 99%